Pendidikan Budi Pekerti pada Kurikulum Sekolah Dasar - Sutjipto -- (Jurnal Pendidikan dan Kebudayaan, 2014)
This article analysed the position of character education within primary school curriculum in Indonesia based on philosophical critical review. The analysis wa carried out using the method of documentation. The results showed that since the post-independence moral education has been strategically placed on the curriculum in Indonesia in three ways, namely stand alone as a subject, combined with relevant subjects, and integrated into other subjects. The domain of character education to fulfill the learners with moral life and character in order to behave well, is considered important to be applied into the primary school curriculum. It is important that implementation efforts to explore habituation, practice, and exemplary environmental conditioning.ABSTRAK Artikel ini mengkaji posisi pendidikan budi pekerti pada kurikulum sekolah dasar di Indonesia didasarkan tinjauan kritis filosofis. Kajian yang dilakukan menggunakan metode studi dokumentasi. Hasil kajian menunjukkan bahwa sejak masa pasca kemerdekaan, pendidikan budi pekerti ditempatkan secara strategis pada kurikulum pendidikan di Indonesia dalam tiga hal, yakni berdiri sendiri sebagai mata pelajaran, digabung dengan mata pelajaran yang relevan, dan terintegrasi ke dalam mata pelajaran lain. Domain pendidikan budi pekerti yang mengisi jiwa peserta didik dengan moral dan akhlak agar bertingkah laku yang baik, penting untuk diwujudkan ke dalam kurikulum sekolah dasar. Yang perlu diperhatikan dalam implementasinya adalah upaya pembiasaan, pengamalan, pengkondisian lingkungan, dan keteladanan.